Private wealth in the Egyptian Late Period: : the tower houses of the Nile delta - Crivelli Montero, Eduardo (Centro de Estudios de Arqueología Histórica (CEAH) de la Universidad Nacional de Rosario, 2021)
During the Egyptian Late Period, in the Nile Delta many huge tower-shaped mud brick buildings were erected. Demographic increase, urbanism, more security and a desire of exhibit prosperity can explain these innovations, along with new roads to wealth (business, financial capital, monetization, etc.) and the weakening of the central State. The Egyptian tower houses are compared with similar constructions of other regions.